2015
DOI: 10.18632/oncotarget.6254
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory bulb proteome dynamics during the progression of sporadic Alzheimer's disease: identification of common and distinct olfactory targets across Alzheimer-related co-pathologies

Abstract: Olfactory dysfunction is present in up to 90% of Alzheimer's disease (AD) patients. Although deposition of hyperphosphorylated tau and β-amyloid substrates are present in olfactory areas, the molecular mechanisms associated with decreased smell function are not completely understood. We have applied mass spectrometry-based quantitative proteomics to probe additional molecular disturbances in postmortem olfactory bulbs (OB) dissected from AD cases respect to neurologically intact controls (n=20, mean age 82.1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 92 publications
2
44
0
1
Order By: Relevance
“…This suggests that an aberrant expression level and/or activity of 14-3-3 proteins in the olfactory bulb of both AD patients and APP/PS1 mice may link to NFT-like structures. In agreement with this study, Zelaya et al noted a decrease in 14-3-3 proteins in the olfactory bulb of human post-mortem AD cases using proteomics [35]. They found an impressing number of deregulated proteins (231) that are involved in dendritic morphogenesis, neuronal injury and axonic distribution.…”
Section: Discussionsupporting
confidence: 84%
“…This suggests that an aberrant expression level and/or activity of 14-3-3 proteins in the olfactory bulb of both AD patients and APP/PS1 mice may link to NFT-like structures. In agreement with this study, Zelaya et al noted a decrease in 14-3-3 proteins in the olfactory bulb of human post-mortem AD cases using proteomics [35]. They found an impressing number of deregulated proteins (231) that are involved in dendritic morphogenesis, neuronal injury and axonic distribution.…”
Section: Discussionsupporting
confidence: 84%
“…First, the significantly altered proteins in rpAD plaques were compared to our database of AD associated proteins identified in previous proteomic studies[1, 2, 4, 11, 13, 14, 22, 3133, 36, 37, 43, 45, 50, 54, 55, 66, 77, 78, 82, 89, 90, 96]. In this database we annotated proteins as up-regulated in AD, down-regulated in AD and proteins that are enriched in plaques or tangles (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This database combined the results from studies that identified proteins in neurofibrillary tangles[50, 66, 82], proteins enriched in plaques[32, 43], proteins that had significantly altered expression in various regions and/or fractions of AD brains in comparison to control brains and proteins that contained the keyword “Alzheimer” in the Uniprot human database[1, 2, 4, 11, 13, 14, 22, 3133, 36, 37, 45, 54, 55, 77, 78, 89, 90, 96]. Protein groups identified in rpAD and sAD plaques were screened against this database to determine how many of the proteins identified in this study have been previously associated with AD pathology.…”
Section: Methodsmentioning
confidence: 99%
“…; Zelaya et al . ), and studies involving animal and cellular models, have largely been covered by previous reviews (Fasano et al . ; Moya‐Alvarado et al .…”
Section: Proteomics Technologymentioning
confidence: 99%